Selection of Reference Genes for Normalization of Real-Time PCR Data in Calliptamus italicus (Orthoptera: Acrididae) Under Different Temperature Conditions. Issue 6 (21st November 2019) - Hu, Hongxia; Ye, Xiaofang; Wang, Han; Ji, Rong
Abstract: Global warming has dominated worldwide climate change trends, and adaptability to high temperatures is the main factor underlying the spread of the pest Calliptamus italicus in Xinjiang Province, China. However, knowledge about the molecular mechanisms responsible for this adaptability and other related biological properties of C. italicus remain relatively unclear. Real-time quantitative polymerase chain reaction (RT-qPCR) is a key tool for gene expression analysis associated with various biological processes. Reference genes are necessary for normalizing gene expression levels across samples taken from specific experimental conditions. In this study, transcript level of five genes ( GAPDH, 18S, TUB, ACT, and EF1α ), commonly used as reference genes, were evaluated under nine different temperatures (27, 30, 33, 36, 39, 42, 45, 48, and 51°C) to assess their expression stability and further select the most suitable to be used on normalization of target gene expression data. Gene expression profiles were analyzed using geNorm, NormFinder, and BestKeeper software packages. The combined results demonstrated that the best-ranked reference genes for C. italicus are EF1α, GAPDH, and ACT under different thermal stress conditions. This is the first study that assesses gene expression analysis across a range of temperatures to select the most appropriate reference genes for RT-qPCR data normalization in C. italicus . These results should assist target gene expression analysis associated with heat stress in C. italicus .